Paclobutrazol enhances yield and secondary compound accumulation in Curcuma longa L. - Montri, N.; Chauytam, S.; Deewatthanawong, R.; Bunya-atichart, K. (International Journal of Agricultural Technology, 2024)
The results indicated that the application of different concentrations of PBZ at 60 days preharvest had an impact on yield after harvest at 9 months while the color of turmeric remained relatively consistent. In all treatments, the rhizome color was yellow to orange. The fresh weight of the rhizome showed no significant differences within the range of 0-800 mg/L PBZ treatments, with the lowest yield observed in 1,200 mg/L PBZ treatment. The dry weight percentage was highest when treated with 800 mg/L PBZ for the mother rhizome and 600 mg/L PBZ for the finger rhizome. Regarding the accumulation of secondary compounds, highly significant differences among the treatments were found for the content of total flavonoids and total phenolics while curcumin showed significant differences. The treatment with 1,200 mg/L PBZ had the highest total phenolics content at 78.18 mg GAE/gDW and total flavonoids at 295.54 mg QUE/gDW. PBZ-treated plants also showed higher curcumin content and percentage than the non-treated plants. These findings indicated that the application of PBZ has the potential to improve both the yield and quality of turmeric, which is advantageous for cultivating this valuable medicinal plant.